Portable infrared camera as a tool in topoclimatic research - Vysoudil, Miroslav (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2009)
The paper presents some possibilities of application of a portable infrared camera for topoclimatic researches, especially for establishing the differences in temperatures of the so-called active surface layer. Demonstrated is the dependence of surface temperature on surface characteristics, such as land use, morphological features and the time of the day. The results can be useful for establishing topoclimatic units with similar temperature regimes.
Keywords: climate; climatology; klimatologija; merjenje; podnebje; temperatura